May the force be with you: an investigation into logging methods using donkeys - Rodrigues, João B.; Garrett, Chris; Norris, Stuart L.; Albuquerque, Francisco; Queijo, Luis; Coelho, João Paulo; Cooke, Fiona; Judge, Andrew (Austral Journal of Veterinary Sciences, 2023)
Working equids represent major sources of energy worldwide, and assume an increasingly important role in line with increasing requirements for sustainable energy. The effectiveness of their contributions relies on welfare, especially in the case of donkeys that, due to their size, face more adverse working conditions compared to larger equids. In this study, heart rate and force exerted were monitored while logging using three methods: direct pull, sled, and vehicles. A swingle tree incorporating a dynamometer and data logger was developed for this project, allowing continuous recording of forces. It was hypothesized that logging techniques that suspend (partially or totally) the load from the ground, reduce the force exerted, thus reducing physical effort. This study also aimed to understand if heart rate can be used as an alternative proxy measure when pulling different loads using different methods. Results showed that the greatest force was measured during direct pull (369.66 N), requiring 20% greater force compared to the sled (299.10 N, P <0.001), and 60% greater force than the vehicle (125.11 N, P <0.001). The sled required an additional 58% of force compared to the vehicle (P <0.001). This determines vehicles are the best option for reducing the force exerted by donkeys. Affordability and skills needed to work with this technique, however, are important considerations. Sleds represent a user-friendly solution; reducing the force needed when compared to direct pull, requiring less skills and equipment. The dynamometer proved an excellent method for force monitoring. Heart rate as a proxy measure for force didn’t provide accurate data for lighter loads. Increasing load weight, followed by the increasing force requirements, correlation and explanatory power became greater, indicating that with heavier logs, or methods that display greater force requirements, heart rate may be used as a proxy method for force, but further studies are needed.